2009
DOI: 10.1021/ja903396e
|View full text |Cite
|
Sign up to set email alerts
|

Exocyclic Delocalization at the Expense of Aromaticity in 3,5-bis(π-Donor) Substituted Pyrazolium Ions and Corresponding Cyclic Bent Allenes

Abstract: Small ring allenes are usually highly strained and highly reactive species, and for a long time considered only as transient intermediates. The recent isolation of a five membered heterocyclic allene 1f has raised questions and debate regarding the factors responsible for its stability. Since 1f has been derived by deprotonation of a pyrazolium ion 2f, it has been suggested that the stability of 1f comes from its aromatic character. Here we report computational evidence, including HOMA and NICS aromaticity ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(51 citation statements)
references
References 46 publications
(28 reference statements)
4
46
0
1
Order By: Relevance
“…The recent revival of carbodiphosphorane chemistry [1][2][3] and the interpretation of CA C H T U N G T R E N N U N G (PR 3 ) 2 as divalent carbon(0) compounds CL 2 [3] in which a carbon atom retaining all four valence electrons as two lone pairs is bonded to two s-donor ligands (Scheme 1) sparked intensive theoretical [4][5][6][7][8][9][10][11] and experimental [10][11][12][13][14] investigations of this hitherto unrecognized class of compounds, which has been the subject of two recent reviews. [15,16] A highlight of this work was the advent of carbodicarbenes CA C H T U N G T R E N N U N G (NHC) 2 as a new type of divalent carbon(0) compounds CL 2 with N-heterocyclic carbenes (NHCs) as ligands, which were theoretically predicted to be stable molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent revival of carbodiphosphorane chemistry [1][2][3] and the interpretation of CA C H T U N G T R E N N U N G (PR 3 ) 2 as divalent carbon(0) compounds CL 2 [3] in which a carbon atom retaining all four valence electrons as two lone pairs is bonded to two s-donor ligands (Scheme 1) sparked intensive theoretical [4][5][6][7][8][9][10][11] and experimental [10][11][12][13][14] investigations of this hitherto unrecognized class of compounds, which has been the subject of two recent reviews. [15,16] A highlight of this work was the advent of carbodicarbenes CA C H T U N G T R E N N U N G (NHC) 2 as a new type of divalent carbon(0) compounds CL 2 with N-heterocyclic carbenes (NHCs) as ligands, which were theoretically predicted to be stable molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Bertrand and co-workers subsequently synthesized [12] the first stable carbodicarbene, while further studies by Fürstner et al [10,13] proved the validity of the carbon(0) concept for this promising class of compounds. [14][15][16] The theoretical studies [4][5][6][7][8][9][10][11] on the electronic structure of compounds CL 2 suggested a wide scale of bonding situations between divalent carbon(0) compounds such as carbodiphosphoranes CA C H T U N G T R E N N U N G (PR 3 ) 2 and carbodicarbenes CA C H T U N G T R E N N U N G (NHC) 2 having two lone-pair orbitals at the central carbon atom and divalent carbon(II) compounds with only one electron lone pair at the carbon atom. [14][15][16] The theoretical studies [4][5][6][7][8][9][10][11] on the electronic structure of compounds CL 2 suggested a wide scale of bonding situations between divalent carbon(0) compounds such as carbodiphosphoranes CA C H T U N G T R E N N U N G (PR 3 ) 2 and carbodicarbenes CA C H T U N G T R E N N U N G (NHC) 2 having two lone-pair orbitals at the central carbon atom and divalent carbon(II) compounds with only one electron lone pair at the carbon atom.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the exocyclic amino group exerts a stronger π-donating effect in the oxidized species 6 than in neutral 4, suggesting the importance of the quinoid-type form 6', despite the fact that this would decrease the aromatic character of the ring. 24 It is worth noting that calculations on the twice-oxidized form of 4c, 22 and X-ray data for the dication of 4a, 7 also support the idea of more localized π-bonding and the importance of structures of type 6' in describing these dications.…”
Section: Introductionmentioning
confidence: 69%
“…Chemie schließlich HOMA-und NICS-Aromatizitätsindizes) zeigten hingegen, [202] dass von 3,5-Bis(p-Donor)-substitutierten Pyrazoliumsalzen abgeleitete Allene nur schwach aromatisch bis nichtaromatisch sind. Noch überraschender gelang uns der experimentelle Nachweis, dass 1) CBA 3 (H + ) mit exocyclischen Aryloxysubstituenten planare endocyclische Stickstoffe aufweisen (Abbildung 11, links), wie man es für ein aromatisches System erwarten würde, und 2) dass CBA 4 (H + ) mit exocyclischen Aminogruppen (mit stärkerem p-Donorvermögen) stark pyramidalisierte endocyclische, aber planarisierte exocyclische Stickstoffzentren aufweist (Abbildung 11, rechts).…”
Section: Methodsunclassified